2020
DOI: 10.1111/sms.13887
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pacing pattern and sub‐technique selection between young and adult competitive cross‐country skiers

Abstract: The present study describes differences in pacing patterns and sub‐technique selection in young compared to adult competitive cross‐country skiers. Eleven young male skiers (YOS) (14.4 ± 0.5 years, trueV˙O2peak 63.9 ± 2.8 mL∙kg‐1∙min‐1) and eight adult male skiers (ADS) (22.6 ± 4.3 years, trueV˙O2peak 77.4 ± 4.4 mL∙kg‐1∙min‐1) performed a free technique rollerski time trial (TT) over a distance of 4.3 km (YOS) and 13.1 km (ADS) to simulate normal racing distances. A GNSS/IMU system was used to track position, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…Poling time, pole swing time and angle between skis and ski push time were different for the two sub-techniques on the same slope-speed condition (G2 vs G4 8% 10 km•h −1 ) and for the different slope-speeds combinations in G2 (8% 10 km•h −1 vs 12% 7 km•h −1 ) and G4 (8% 10 km•h −1 vs 2% 21 km•h −1 ). As these parameters differ both between sub-techniques and between speed/slope for a given sub-technique, it can be speculated that these parameters are main drivers with respect to preferred choice of sub-technique between G2 and G4 for a given slope and speed (Sollie et al, 2021). Nevertheless, as athletes normally use G3 between G2 and G4, the 8% slope and 10 km•h −1 speed may be more appropriate for the G3 sub-technique.…”
Section: Discussionmentioning
confidence: 99%
“…Poling time, pole swing time and angle between skis and ski push time were different for the two sub-techniques on the same slope-speed condition (G2 vs G4 8% 10 km•h −1 ) and for the different slope-speeds combinations in G2 (8% 10 km•h −1 vs 12% 7 km•h −1 ) and G4 (8% 10 km•h −1 vs 2% 21 km•h −1 ). As these parameters differ both between sub-techniques and between speed/slope for a given sub-technique, it can be speculated that these parameters are main drivers with respect to preferred choice of sub-technique between G2 and G4 for a given slope and speed (Sollie et al, 2021). Nevertheless, as athletes normally use G3 between G2 and G4, the 8% slope and 10 km•h −1 speed may be more appropriate for the G3 sub-technique.…”
Section: Discussionmentioning
confidence: 99%
“…Cross country (XC) skiing is a demanding and complex whole-body endurance sport that consists of races performed on undulating terrain with highly varying exercise intensity and complex interactions in energy system contributions ( Gløersen et al, 2020 ; Sollie et al, 2020 ). Physiological determinants including peak oxygen uptake (V̇O 2peak ) ( Sandbakk et al, 2011 ; Losnegard et al, 2013 ; Sandbakk et al, 2016 ), the ability to efficiently transform metabolic energy into speed (e.g., gross efficiency (GE)) ( Losnegard et al, 2013 ) , ( Sandbakk et al, 2010 ) and the ability to repeatedly perform, and recover from, efforts above the V̇O 2peak ( Gløersen et al, 2020 ; Sollie et al, 2020 ) are all important for XC skiing performance. Depending on the race length, sub-technique used and the technical ability of the skiers, a certain level of strength also seems necessary to optimize performance ( Losnegard et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…In classical AB XC skiing, it has been suggested that there are speed [ 6 , 17 , 18 ] and incline [ 11 , 12 , 16 ] thresholds for the use of the sub-techniques. Additionally, the skiers’ physical capacity will influence the speed and choice of sub-technique [ 19 , 20 ]. In this context, the ability to use the different sub-techniques may additionally be dependent on functional limitations related to the individual disability among standing Para XC skiers.…”
Section: Introductionmentioning
confidence: 99%